Control de inventarios y su impacto en la gestión comercial de la empresa Multicomercio Ambato de la ciudad de Guaranda provincia Bolívar en el año 2017 - Ramirez Velastegui, Mishell Antonela (2018)
The present investigation was executed in the city of Guaranda, with the purpose of improving the control of inventories and the commercial management of the company Multicomercio Ambato, proceeding to the formulation of the research topic called: CONTROL OF INVENTORIES AND ITS IMPACT ON COMMERCIAL MANAGEMENT OF THE MULTICOMERCIO AMBATO COMPANY OF THE CITY OF GUARANDA PROVINCIA BOLÍVAR IN THE YEAR 2017, surveys were also carried out to 5 workers, to know the knowledge that they had about the inventories; and an interview with the owner of the company to learn about relevant aspects of the inventory management carried out by the company, whose main objective was to examine the current situation of the company Multicomercio Ambato, in the city of Guaranda Provincia Bolívar so that the research is developed in its entirety and in a successful manner, a descriptive research was carried out which will help us to evaluate the processes carried out by the Ambato Multicomercio Company as well as its results and to be able to describe the anomalies that exist today in day in the organization with respect to the control of inventories and how it affects the commercial management of the same, a Qualitative Investigation was made in which reference is made to the characteristics that were evident during the research process, as well as at the time of the compilation of information where Landlord and Landlords were involved to Company. Through this process of control it was possible to directly evidence the behavior of each of the individuals who participated in the research prior to that, a Historical Investigation was carried out, which will allow us to describe the phenomena that occurred in the company's past Ambato Multicomercio with respect to the control of inventories, which serves to base us on historical sources and to analyze the pertinent information, to have a broad idea of the situation that we are investigating and finally a Bibliographic Investigation was done where you can know more about The subject is analyzed through several criteria that have been presented by several authors and that are cited in scientific theory, with the purpose of selecting relevant information to support the research that is being carried out. At the end of this investigation, it was established that the company Multicomercio Ambato does not have adequate control of the inventory by the owner as well as its XVI workers where it is concluded that it is of great importance to implement strategies for the improvement of inventory control and in this case will be developed an inventory system where they will have their respective codes and number of existing stocks in warehouses for sale improving the commercial management of the company and facilitating the work to all those who integrate it